Therapeutic efficacy of artemether–lumefantrine for the treatment of uncomplicated Plasmodium falciparum malaria from three highly malarious states in India. (December 2016) - Bharti, Praveen; Shukla, Man; Ringwald, Pascal; Krishna, Sri; Singh, Pushpendra; Yadav, Ajay; Mishra, Sweta; Gahlot, Usha; Malaiya, Jai; Kumar, Amit; Prasad, Shambhu; Baghel, Pradeep; et al.
Abstract Background Anti-malarial drug resistance continues to be a leading threat to malaria control efforts and calls for continued monitoring of waning efficacy of artemisinin-based combination therapy (ACT). Artesunate + sulfadoxine/pyrimethamine (AS + SP) is used for the treatment of uncomplicatedPlasmodium falciparum malaria in India. However, resistance against AS + SP is emerged in northeastern states. Therefore, artemether–lumefantrine (AL) is the recommended first line treatment for falciparum malaria in north eastern states. This study investigates the therapeutic efficacy and safety of AL for the treatment of uncomplicated falciparum malaria in three malaria-endemic states in India. The data generated through this study will benefit the immediate implementation of second-line ACT as and when required. Methods This was a one-arm prospective evaluation of clinical and parasitological responses for uncomplicated falciparum malaria using WHO protocol. Patients diagnosed with uncomplicated monoP. falciparum infection were administered six-dose regimen of AL over 3 days and subsequent follow-up was carried out up to 28 days. Molecular markersmsp -1 andmsp -2 were used to differentiate recrudescence and re-infection and K13 propeller gene was amplified and sequenced covering the codon 450–680. Results A total of 402 eligible patients were enrolled in the study from all four sites. Overall, adequate clinical and parasitological response (ACPR) was 98 % without PCR correction and 99 % with PCR correction. At three study sites, ACPR rates were 100 %, while at Bastar, cure rate was 92.5 % on day 28. No early treatment failure was found. The PCR-corrected endpoint finding confirmed that one late clinical failure (LCF) and two late parasitological failures (LPF) were recrudescences. The PCR corrected cure rate was 96.5 %. The mean fever clearance time was 27.2 h ± 8.2 (24–48 h) and the mean parasite clearance time was 30.1 h ± 11.0 (24–72 h). Additionally, no adverse event was recorded. Analysis of total 186 samples revealed a mutation in thek13 gene along with non-synonymous mutation at codon M579T in three (1.6 %) samples. Conclusion AL is an efficacious drug for the treatment of uncomplicated falciparum malaria. However, regular monitoring of AL is required in view of malaria elimination initiatives, which will be largely dependent on therapeutic interventions, regular surveillance and targeted vector control.